COVID-19: a modern trigger for Guillain-Barre syndrome, myasthenia gravis, and small fiber neuropathy - Gomez, Francisco; Mehra, Ashir; Ensrud, Erik; Diedrich, Daniel; Laudanski, Krzysztof (Frontiers in Neuroscience, 2023)
COVID-19 infection has had a profound impact on society. During the initial phase of the pandemic, there were several suggestions that COVID-19 may lead to acute and protracted neurologic sequelae. For example, peripheral neuropathies exhibited distinctive features as compared to those observed in critical care illness. The peripheral nervous system, lacking the protection afforded by the blood–brain barrier, has been a particular site of sequelae and complications subsequent to COVID-19 infection, including Guillain-Barre syndrome, myasthenia gravis, and small fiber neuropathy. We will discuss these disorders in terms of their clinical manifestations, diagnosis, and treatment as well as the pathophysiology in relation to COVID-19.